E2~Ub conjugates regulate the kinase activity of Shigella effector OspG during pathogenesis. (20th January 2014) - Pruneda, Jonathan N; Smith, F Donelson; Daurie, Angela; Swaney, Danielle L; Villén, Judit; Scott, John D; Stadnyk, Andrew W; Le Trong, Isolde; Stenkamp, Ronald E; Klevit, Rachel E; Rohde, John R; Brzovic, Peter S
Synopsis <boxed-text content-type="graphic" id="embj201386386-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> The crystal structure of a complex between ubiquitin‐loaded UbcH5c and the Shigella effector kinase OspG shows how they regulate each other, and has allowed to demonstrate the role of this interaction in repressing host innate immune responses. Structure of the Shigella effector kinase OspG in complex with an activated UbcH5˜Ub conjugate reveals an unusual regulatory role for E2˜Ubs. OspG is a minimal kinase domain that requires binding to E2˜Ub conjugates to stimulate ATP binding and kinase activity. OspG can interact with a subset of related E2˜Ub conjugates. The structure of a stable UbcH5˜Ub conjugate in the OspG complex is compared to structures of UbcH5˜Ub poised for Ub transfer. Mouse models of Shigellosis show binding to host E2˜Ubs is required for OspG activity.